Prevalence and zoonotic potential of canine hookworms in Malaysia - Mahdy, Mohammed A.K.; Lim, Yvonne Ai Lian; Ngui, Romano; Fatimah, M.R.S.; Choy, Seow Huey; Yap, Nan Jiun; Al-Mekhlafi, Hesham Mahyoub; Ibrahim, Jamaiah; Surin, Johari (BMC, 2012)
Background: Canine hookworm infection is endemic in Southeast Asian countries with a prevalence ranging from 70% to 100%, with zoonotic transmission representing a potentially significant public health concern. However, there are limited data available on the prevalence of canine hookworms in Malaysia. This study was conducted to determine the prevalence of hookworm and Ancylostoma species among dogs in Malaysia.